The impact of service quality dimensions on the Jordanian private medical laboratory performance - Aldaaeeq, Mohammed Omar; Abu Hussein, Al-Harith Mohammed (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to examine the impact of service quality dimensions on the performance of private Jordanian medical laboratories The study focused on the quality of laboratory services provided by private medical laboratories in Jordan and its impact on patient satisfaction and loyalty. Poor service quality in some private laboratories affects patients’ satisfaction and loyalty, which necessitates a study to assess the extent to which these dimensions influence patients. The study seeks to redefine and highlight the different dimensions of laboratory service quality, including tangibility, reliability, assurance, empathy, and responsiveness, and to evaluate the influence each dimension has on patient satisfaction and loyalty Moreover, the study sought to provide recommendations for improving service quality and enhancing patient satisfaction and loyalty. The study is based on hypothesis testing regarding the impact of service quality dimensions on patient satisfaction and loyalty in private medical laboratories in Jordan. A descriptive-analytical approach was adopted for the study; data were collected through a questionnaire that was the main tool to achieve the aims from a sample of patients visiting private medical laboratories in Jordan. These data were analyzed using descriptive statistical methods and statistical tests in an attempt to understand the influence of service quality dimensions on satisfaction and loyalty among the patients. The study population consists of all patients of private Jordanian medical laboratories operating in Amman city and registered with the Jordan Ministry of Health. This includes 332 laboratories, of which 292 are private laboratories and 40 belong to private hospitals. The study sample consists of 400 patients, who were selected randomly. In order to achieve the study’s objectives, a questionnaire was developed based on relevant literature to measure the study variables. To answer the study questions and test its hypotheses, a set of statistical techniques was used, including descriptive statistics, normal distribution, Pearson correlation, and simple and multiple regression.